Aerobic Exercise Modulates Visceral Adipose Tissue of Estrogen Deprived Rats in an Experimental Model of Dyslipidemia - Magalhães, Walkyria Villegas; Chucata, Kemily Loren Barros; Dsouki, Nuha Ahmad; Nucci, Ricardo Aparecido Baptista; Veloso, Aparecida Gabriela Bexiga; Fonseca, Fernando Luiz Affonso; Maifrino, Laura Beatriz Mesiano (Journal of Health and Allied Sciences NU, 2023)
Introduction Menopausal women have an increase deposition of body fat and changes in the lipid profile, being especially susceptible to cardiovascular diseases, and type 2 diabetes. However, physical activity can mitigate this situation. Thus, the aim of the present study is to evaluate the effects of moderate aerobic exercise on visceral adipose tissue (VAT) of female LDL-receptor knockout ovariectomized mice. Methods We used 48 animals, divided into six groups (n = 8/per group): sedentary control (SC), sedentary ovariectomized control (SCO), trained ovariectomized control (TCO), sedentary non-ovariectomized LDL-receptor knockout (KS), sedentary ovariectomized LDL-receptor knockout (KOS), and trained LDL-receptor knockout ovariectomized (KOT). We analyzed the VAT through morphometric and stereological parameters in hematoxylin and eosin stained sections. Additionally, we evaluated biochemical parameters as glucose, triglycerides, and total cholesterol. Finally, immunohistochemical techniques for matrix remodeling, inflammation, apoptosis, and oxidative stress were evaluated. Results We observed that menopause is related to increased visceral adiposity, inflammation, oxidative stress, macrophages activity, serum levels of glucose, triglycerides, and total cholesterol. However, exercise was effective in reducing these parameters, as well as being associated with increased vascularization of VAT and interstitial volume density. Conclusions Moderate exercise is a key factor in mitigating the effects of dyslipidemia in estrogen deprivation. However, further studies are needed to corroborate with our findings.
Keywords: adiposity; dyslipidemia; experimental; menopause; treadmill